2007
DOI: 10.1037/0893-164x.21.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco cessation in alcohol-dependent smokers: Analysis of real-time reports.

Abstract: Alcohol-tobacco interactions and relapse precipitants were examined among alcohol-dependent smokers in a trial of concurrent alcohol and tobacco treatment. After discharge from treatment, participants completed 14 days of electronic diary (ED) assessments of mood, self-efficacy, urges to drink or smoke, and drinking and smoking behavior. ED data revealed an increase in frequency of alcohol urges after smoking episodes. Drinking relapse episodes were predicted by prior ED ratings of low self-efficacy to resist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 50 publications
4
88
1
1
Order By: Relevance
“…Ambulatory monitoring techniques such as the Experience Sampling Method (ESM) or Ecological Momentary Assessment (EMA) have been increasingly applied over the last decade to study of a range of psychiatric disorders, including mood disorders (Myin-Germeys et al, 2003;Peeters et al, 2006), psychosis (Delespaul et al, 2002;deVries and Delespaul, 1989;Granholm et al, 2007;Kimhy et al, 2006;Myin-Germeys et al, 2001, personality disorders (Ebner-Priember et al, 2006;Farmer et al, 2004;Loewenstein et al, 1987;Stein, 1996), eating disorders (Hilbert and Tuschen-Caffi er, 2007;Smyth et al, 2007;Stein and Corte, 2003), social anxiety (Brown et al, 2007;Kashdan and Steger, 2006;Lee et al, 2006) and substance use (Cooney et al, 2007;Freedman et al, 2006;Hopper et al, 2006;Krahn et al, 2005;Lukasiewicz et al, 2005;Swendsen et al, 2000). A principal advantage of this approach is that it allows researchers to assess symptom expression in a manner that is often inaccessible to standard hospital or laboratory protocols, and to model complex within-person processes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Ambulatory monitoring techniques such as the Experience Sampling Method (ESM) or Ecological Momentary Assessment (EMA) have been increasingly applied over the last decade to study of a range of psychiatric disorders, including mood disorders (Myin-Germeys et al, 2003;Peeters et al, 2006), psychosis (Delespaul et al, 2002;deVries and Delespaul, 1989;Granholm et al, 2007;Kimhy et al, 2006;Myin-Germeys et al, 2001, personality disorders (Ebner-Priember et al, 2006;Farmer et al, 2004;Loewenstein et al, 1987;Stein, 1996), eating disorders (Hilbert and Tuschen-Caffi er, 2007;Smyth et al, 2007;Stein and Corte, 2003), social anxiety (Brown et al, 2007;Kashdan and Steger, 2006;Lee et al, 2006) and substance use (Cooney et al, 2007;Freedman et al, 2006;Hopper et al, 2006;Krahn et al, 2005;Lukasiewicz et al, 2005;Swendsen et al, 2000). A principal advantage of this approach is that it allows researchers to assess symptom expression in a manner that is often inaccessible to standard hospital or laboratory protocols, and to model complex within-person processes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies established a link between an elevated negative affect, smoking urges, and a relapse of 3 hr (Cooney et al, 2007), 2 hr (Berkman et al, 2011), and 15 min (Cooney et al, 2007) prior to smoking. Berkman et al (2011) reported no effect of mood 4 hr prior to a relapse, whereas Shiffman and Waters (2004) reported rising negative affect some 6 hr before a subsequent lapse.…”
Section: Triggers Of Smoking and Prediction Of Cessation Successmentioning
confidence: 99%
“…Accordingly, it is not surprising that EMA methods are being widely applied to studies of tobacco use, particularly smoking. EMA methods have been used to study antecedents and consequences of smoking in adolescents (Mermelstein, Hedeker, & Wesintein, 2010) and adults (Carter et al, 2010;Warthen & Tiffany, 2009), in smokers with posttraumatic stress disorder and other disorders (Beckham et al, 2008;Epstein, Marrone, Heishman, Schmittner, & Preston, 2010;Piper, Cook, Schlam, Jorenby, & Baker, 2011), during ad libitum smoking (Shapiro, Jamner, Davydov, & James, 2002) and smoking cessation (Bolt, Piper, Theobald, & Baker, 2012;Cooney et al, 2007;Minami, McCarthy, Jorenby, & Baker, 2011), and in relation to a range of variables ranging from alcohol use (Holt, Litt, & Cooney, 2012;Piasecki, Wood, Shiffman, Sher, & Heath, 2012;Witkiewitz et al, 2012) to worried thoughts about smoking (Magnan, Köblitz, McCaul, & Dillard, 2013), and exposure to media messages (Shadel, Martino, Setodji, & Scharf, 2012) or proximity to tobacco sales outlets (Kirchner, Cantrell, et al, 2013). EMA methods have also been fruitfully applied to study the effects of treatment, both to define treatment outcome (Shiffman et al, 2000;Shiffman et al, 2006) and to examine the processes that mediate treatment effects (Ferguson, Shiffman, & Gwaltney, 2006;McCarthy et al, 2008;Piper et al, 2008).…”
Section: Ema In Tobacco Researchmentioning
confidence: 99%